STRATEGI DESTINATION BRANDING EVENT BUDAYA PEMERINTAH KOTA BANDUNG SEBAGAI MAGNET PARIWISATA - Ita Suryani; Teguh Tri Susanto (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
Bandung is known as a tourist destination because it has a lot of potential that supports the tourism sector. Of uniqueness their culture, culinary, location shopping interesting, city environment share, until a panorama its natural a stunning. In improving the number of visits local tourists and foreign tourists, the city government bandung do strategy destination branding carried out to educate potential wisatanya to be more known through slogan â€œstunning bandungâ€ which was launched in 2016. The method used for this research is the case study method is a research method that uses a variety of data sources that can be used to examine, comprehensive describe and explain the various aspects of individual, group, program, organization or event systematical. Conclusions shows that strategy destination branding needs to be done to educate tourism potential bandung city to be more known by local and international tourists , and is expected to strategy branding destinations this can serve as a magnet tourism and make bandung city as a tourist destination primadonna in Indonesia .